Performance Analysis of the Office of Small and Medium Enterprises Cooperatives in Labuhanbatu Regency - Salpiani Munthe; Marliyah Marliyah (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2022)
This study aims to analyze the performance of the MSME Cooperative Office in Labuhanbatu Regency in carrying out the main tasks and functions of cooperative development. This study uses descriptive research with qualitative data assessment. In collecting data, researchers used interviews, observation and documentation. The results of this study indicate that the performance of the Department of Cooperatives of UMKM in Labuhanbatu Regency in carrying out the main tasks and functions of fostering cooperatives is still less than optimal. Then there are factors that influence the performance found in the field, namely human resource factors and cooperative development factors that have an impact on the performance of the MSME Cooperative Office in Labuhanbatu Regency in carrying out the duties and functions of cooperative development.